Advanced Battery‐Type Anode Materials for High‐Performance Sodium‐Ion Capacitors. Issue 10 (2nd September 2020) - Deng, Xinglan; Zou, Kangyu; Cai, Peng; Wang, Baowei; Hou, Hongshuai; Zou, Guoqiang; Ji, Xiaobo
Abstract: High‐efficiency energy storage technologies and devices have gained numerous attention because of their ever‐increasing requirement. Sodium‐ion capacitors (SICs), as a burgeoning electrochemical energy storage device, combine virtues of rechargeable batteries and electrochemical double layer supercapacitors, delivering both high energy–power density and long cycling life. In the past decades, great efforts have been made to find suitable anode material to conquer the kinetic imbalance between the battery‐type anode with sluggish bulk redox reaction and the capacitor‐type cathode with fast ion absorption/desorption process. By exploring high‐rate performance anode materials, the great reaction kinetic gap between cathodes and anodes can be narrowed down, which directly affects the energy–power densities of SICs. In this article, an overview of advanced battery‐type anode materials is offered for high‐performance SICs with an emphasis on anode structural design and improved energy–power density, including carbonaceous materials, metallic compounds, MXene, organic polymers, and so on. Furthermore, the implementation of presodiation for the sake of optimizing the SICs is also illustrated. Finally, the challenges faced and the perspectives for future developing trends of SICs are discussed. Abstract : This review summarizes the recent progress on anode materials for sodium‐ion capacitors (SICs), including carbonaceous materials, metallic compounds, MXene, and organic polymers; then, the implementation of presodiation for the sake of optimizing the SICs is also illustrated; and finally, the challenges and future prospects for SIC researches are proposed.